Caractéristiques syntaxiques de la parenthèse en latin : linéarisation, délimitation et insertion - Isabelle Charnavel (Discours)
The aim of the paper is to analyse the syntactic rules of the incidental clause in Latin: indeed, the incidental – i.e. parenthetical sentence - exhibits the following paradox: although it is independent from a structural viewpoint (it constitutes a main clause), it is inserted in another sentence from a syntagmatic viewpoint (it linearly occurs inside another sentence, the host). I propose that despite its syntactic autonomy the incidental obeys precise syntactic contraints of insertion.First of all, I show that the incidental, which is always continuous, is delimited on both boundaries, even if it does not have any specific marker: the clause change marks the beginning of the incidental whereas the host start marks its end, by means of repetitions that may lead to anacoluthons.Furthermore, I argue that the position of the incidental in the host sentence obeys specific rules. First, the insertion spots are constrained: they occur between the functional groups of the host sentence. Moreover, there are distributional contraints to decide which insertion spot to use. I propose that the domain of the incidental consists of the constituent(s) over which the incidental semantically scopes and that it always occurs inside or on the periphery of its domain: the incidental to a root clause occurs at the second position of its domain, whereas the incidental to a phrase is on its right border.